Current status of audiovisual translation in Colombia - Orrego, Jefferson David; Alarcón, Natalia; Olaya, Claudia Lorena; Pérez, Katherin (Íkala, Revista de Lenguaje y Cultura, 2010)
This article has two objectives: to present the general view of the current market of Audio Visual Translation (AVT) in Colombia and to highlight the importance of developing further studies in this area. The methodology used included research and reading literature related to the subject, the implementation of surveys to different groups related to AVT and subsequent analysis. The results showed the general lack of knowledge in this discipline and the preferences for AVT modalities of the surveyed groups. It was observed that each group has a marked preference for subtitling due to specific reasons. It was concluded that Colombian translators need AVT training to meet the market demands and the importance of developing further and deeper studies focused on the development of AVT in Colombia is highlighted.